Effects of Coenzyme Q10 Supplemented to Culture Medium on Morphology of Mouse Early Embryonic Development as a Model for Human Being - Fakhrildin, Muhammad Baqir MR; Abdulhussein, M. Mudhafar (International Journal of Psychosocial Rehabilitation, 2020)
Background: Zygote produce from once a sperm fertilizes an egg cell. Then, the zygote will begin chain of cellular cleavages to produce multicellular mass, its embryo, than differentiation to different tissues and organism. Coenzyme Q10, is an antioxidant produced in the body. It boosts cellular energy and may enhance the immune system. CoQ10 is present and measurable in seminal fluid, the concentration of CoQ10 directly correlates with both sperm count and motility. It is beneficial in the prevention and treatment a wide range of health problems. Objectives: The present study was aimed to investigate the possibility of using coenzyme Q10 to improve early embryonic development (ED) in mice as a model for human being. Materials and Methods: Superovulation program was preformed to mature healthy female mice with age 10-12 weeks and weight 24-26 gm. After sacrificing superovulated female, oocytes were collected and incubated within CO2 incubator for less than 1 hour. Also, sperm were collected from vas deference of males. Then sperm parameters were assessed after 30 min. of incubation. Mature oocytes were divided to three groups according toconcentrations of CoQ10 including G1 (control group; SMART medium only), G2 (treated group; SMART medium enriched with 20 M CoQ10) and G3 (treated group; SMART medium enriched with 40 M CoQ10). IVF technique was performed for all groups, and assessment of IVF (%), embryonic development stage (%) and abnormal embryo morphology (%) for each embryo stage. Results: Results of the present study appeared non significant differences (P>0.05) in the 8-cells stage were assessed among control and treated groups. Within same stage, percentages of abnormal morphology were significantly decreased (P